Optimized profit repatriation in multinational enterprises through cross-border change of legal form and international tax management - Thomas Kollruss (Heliyon, 2023)
This article shows for the first time that the cross-border change of legal form can be used for tax-optimized profit repatriation. By means of a cross-border change of legal form of the foreign EU corporation prior to distribution into another foreign EU corporation with subsequent dividend distribution after the cross-border change of legal form has taken place, the taxation of dividends with withholding tax can be avoided. This study develops and discusses this strategy for the first time and transfers it specifically to U.S. shareholders of European corporations. Moreover, this strategy is relevant in general for all shareholders of European corporations, irrespective of their residence, to get tax-optimized profit repatriation of dividends (retained earnings) and to avoid the problem of treaty shopping, which has been significantly strengthened by the introduction of the ATAD/BEPS principal purpose test (PPT) in all EU Member States. The study extends the state of knowledge in the area of international taxation, international mergers, finance and strategy.